Effect of Use of Sodium Hydroxide (NaOH) on Geopolymer Making Using Perlit Materials, Basalt, Feldspart - Muhammad (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Research was conducted on the manufacture of geopolymers with pearlite, basalt and feldspart materials with variations of NaOH 15 M, 25 M, 35 M and 45 M. In this study, we will know the effect of using NaOH in the manufacture of geopolymers. Variables in this study included percent of total use of pearlite, basalt and pearlite and variations in NaOH molarity. Geopolymers are environmentally friendly materials that are commonly developed as alternative materials to replace conventional cement. The results of physical analysis in this study that carried out measurements were absorption, porosity, fuel shrinkage, dry bulk density. Based on the research, the lowest fuel shrinkage value was obtained using feldspart material with 200 mesh fineness, at 2.11%, the lowest porosity value using basalt material with 35 M NaOH which was 20.73%, the lowest absorption value was obtained using basalt material with NaOH 45 M variation is 11.17% and the highest dry bulk density test results are using basalt material with 45 M NaOH variation with a value of 1.88 gr / cm3. Based on the results of the research variations of NaOH affect the absorption and porosity values ​​which are increasingly the percentage of addition of NaOH, the value of absorption and the value of porosity are getting smaller and the density becomes higher so that the strength of geopolymers increases.